Sustainable Sales: Five Legs Resto's Green Marketing Mix and Social Media Impact – A Mataram City Case Study - Rusiyati, Sri; Suleman, Dede; Zuniarti, Ida; Puspasari, Aprilia; Sofyanty, Devy; Hakim, Lukman (Dinasti Publisher, 2024)
This research investigates the application of Green Marketing strategies in the Five Legs Resto, Mataram City, Lombok, and assesses their impact on both traditional product sales and social media influence. Drawing on a comprehensive green marketing mix, including green product, price, place, and promotion, the study employs regression analyses to unravel the intricate relationships among these variables. The findings reveal that eco-friendly product offerings and transparent pricing positively influence product sales and social media influence. Conversely, the physical location (Green Place) does not significantly impact the outcomes, suggesting the growing importance of online channels. Notably, effective green promotion emerges as a powerful driver of both product sales and social media influence. These results contribute to the existing literature on green marketing and offer actionable insights for businesses seeking a balance between environmental responsibility and commercial success. The implications extend to both academic research and practical considerations, guiding future explorations in the dynamic landscape of sustainability-oriented marketing.